2011
DOI: 10.1186/1471-2180-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iclR and arcA knockouts on biomass formation and metabolic fluxes in Escherichia coli K12 and its implications on understanding the metabolism of Escherichia coli BL21 (DE3)

Abstract: BackgroundGene expression is regulated through a complex interplay of different transcription factors (TFs) which can enhance or inhibit gene transcription. ArcA is a global regulator that regulates genes involved in different metabolic pathways, while IclR as a local regulator, controls the transcription of the glyoxylate pathway genes of the aceBAK operon. This study investigates the physiological and metabolic consequences of arcA and iclR deletions on E. coli K12 MG1655 under glucose abundant and limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 70 publications
3
94
1
Order By: Relevance
“…When IclR is inactivated, repression of the expression glyoxylate genes is released, and the glyoxylate pathway is activated. This strategy could be used to reduce the flux through the TCA cycle (15). PG05/H7 (△sucA△poxB::acs△aceA) and PG07/H7 (△sucA△poxB::acs△iclR) were constructed to investigate the effects of increasing glyoxylate pathway on DAOCS catalyzed reactions.…”
Section: Resultsmentioning
confidence: 99%
“…When IclR is inactivated, repression of the expression glyoxylate genes is released, and the glyoxylate pathway is activated. This strategy could be used to reduce the flux through the TCA cycle (15). PG05/H7 (△sucA△poxB::acs△aceA) and PG07/H7 (△sucA△poxB::acs△iclR) were constructed to investigate the effects of increasing glyoxylate pathway on DAOCS catalyzed reactions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in l-lysine fermentation, a reduced carbon flux was expected to increase the l-lysine-production yield [42], and higher carbon flux into the TCA cycle is expected to lead to higher l-glutamic acid production [31]. In E. coli, arcA gene deletion increases the carbon flux into the TCA cycle [13], and we confirmed that this deletion (ΔarcA) indeed improves l-glutamic acid production in the E. coli MG1655 ΔsucA strain (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…To validate our method, we chose the ArcAB two-component regulatory system of Escherichia coli, as ArcAB regulates the bacterial transition from aerobic to anaerobic growth and controls more than 100 genes involved in the TCA cycle and energy metabolism [12,13]. DNA-array data for both arcA and arcB gene-deletion strains were used to classify genes with increased expression levels in ΔarcA and ΔarcB strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…More specific details about the metabolic flux calculations can be found in (Waegeman et al, 2011a) www.intechopen.com…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Furthermore, only a small part of the tremendously elevated biomass yield was attributed to increased glycogen content (Waegeman et al, 2011a) making this strain an attractive candidate for recombinant protein production.…”
Section: Wwwintechopencommentioning
confidence: 99%